2006
DOI: 10.1189/jlb.1204748
|View full text |Cite
|
Sign up to set email alerts
|

A selective small molecule agonist of the melanocortin-1 receptor inhibits lipopolysaccharide-induced cytokine accumulation and leukocyte infiltration in mice

Abstract: It is well established that melanocortins are peptides that have potent anti-inflammatory activity. Recent research has focused on understanding which of the known melanocortin receptors mediates the anti-inflammatory actions of the melanocortins. The aim of this study was to assess the anti-inflammatory activity of a synthetic MC-1R agonist. BMS-470539 is a potent, selective, full agonist of human and murine MC-1R with EC(50) values in a cAMP accumulation assay of 16.8 and 11.6 nM, respectively. BMS-470539 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 32 publications
(39 reference statements)
1
38
0
Order By: Relevance
“…Additional studies were conducted to determine whether f-LIGRL-NH 2 -induced inhibition of neutrophil infiltration was modulated by cotreatment with the glucocorticoid dexamethasone. In these studies, pretreatment of lipopolysaccharide-exposed mice with dexamethasone alone was associated with reduced BAL neutrophil numbers, as previously demonstrated by others (Lefort et al, 2001;Birrell et al, 2004;Kang et al, 2006;Moschos et al, 2007). Of particular interest, the inhibitory effect of f-LIGRL-NH 2 on neutrophil infiltration in lipopolysaccharide-exposed mice was significantly greater in mice that were cotreated with dexamethasone.…”
Section: Influence Of Dexamethasone On Par 2 Function In Airways 627supporting
confidence: 67%
“…Additional studies were conducted to determine whether f-LIGRL-NH 2 -induced inhibition of neutrophil infiltration was modulated by cotreatment with the glucocorticoid dexamethasone. In these studies, pretreatment of lipopolysaccharide-exposed mice with dexamethasone alone was associated with reduced BAL neutrophil numbers, as previously demonstrated by others (Lefort et al, 2001;Birrell et al, 2004;Kang et al, 2006;Moschos et al, 2007). Of particular interest, the inhibitory effect of f-LIGRL-NH 2 on neutrophil infiltration in lipopolysaccharide-exposed mice was significantly greater in mice that were cotreated with dexamethasone.…”
Section: Influence Of Dexamethasone On Par 2 Function In Airways 627supporting
confidence: 67%
“…Although there has been controversies over the importance of MC1-R in modulating inflammatory responses in the skin, 20,21 several studies have shown that selective activation of the MC1-R by pharmacological means suppresses inflammatory responses in other disease models, such as vasculitis and lung inflammation. 22,23 However, to the best of our knowledge, no study has ever demonstrated that deficient MC1-R function is inherently associated with inflammation. Accordingly, the data on the inflammatory profile of MC1R e/e mice provide novel insights into the role of MC1-R as a physiological regulator of inflammatory responses.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Conversely, selective MC1-R and MC3-R agonists exert anti-inflammatory actions and put in motion proresolving processes. [10][11][12][13] Recent data also indicate that MC1-R activation in an inflamed vasculature can inhibit cell adhesion and migration by acting on the adherent leukocytes and reduce the levels of a variety of chemokines, which are known to contribute to the pathogenesis of atherosclerosis. However, these findings have been exclusively derived from acute experiments such as vascular and cardiac ischemia/reperfusion models, whereas the potential of MC1-R and MC3-R activation in chronic inflammatory conditions such as atherosclerosis remains unexplored.…”
mentioning
confidence: 99%